Introduction to computable general equilibrium models - Burfisher, Mary E. (New York, NY Cambridge University Press, 2016)
"This book provides an accessible, undergraduate-level introduction to computable general equilibrium (CGE) models, a class of model that has come to play an important role in government policy decisions. The book uses a graphical approach to explain the economic theory that underlies a CGE model, and provides results from simple, small-scale CGE models to illustrate the links between theory and model outcomes. The book includes eleven guided, hands-on exercises that introduce modeling techniques that are applied to real-world economic problems. Students will learn how to integrate their separate fields of economic study into a comprehensive, general equilibrium perspective as they develop their skills as producers or consumers of CGE-based analysis."--Provided by publisher.
Includes bibliographical references (pages 407-418) and indexes.
Keywords: Computable general equilibrium models; Equilibrium (Economics) -- Mathematical models